Innovative MBR-RO processes for reclamation of municipal wastewater to high-grade product water - Wang, Siyu (Nanyang Technological University, 2022)
Freshwater resilience is facing to an increasing challenge, while carbon neutral wastewater reclamation has been put onto agenda in more and more countries. Currently, the most prevailing municipal wastewater reclamation process is the integrated conventional activated sludge-microfiltration-reverse osmosis (CAS-MF-RO) process, which is associated with high energy demand, large land use, excessive sludge generation and substantial greenhouse gas (GHG) emissions. Apparently, such a wastewater reclamation process could not offer a sustainable engineering solution towards future water sustainability. Therefore, this study aimed to develop novel municipal wastewater reclamation processes with focus on water-energy-greenhouse gas nexus. Membrane bioreactor (MBR) process is gaining more and more interest due to its high effluent quality, long sludge retention time and small footprint. However, the large-scale application of traditional suspended sludge MBR has been largely restricted due to the rapid membrane fouling. Therefore, in the first phase of study, a moving bed ceramic membrane bioreactor (MBCMBR) coupled with reverse osmosis (RO) was developed for municipal wastewater reclamation. The results obtained under different dissolve oxygen (DO) conditions showed that more than 99.7% of COD and 96.7% of total nitrogen were removed in the MBCMBR-RO process. It was demonstrated that the product water could meet the typical NEWater quality of Singapore and the Chinese Class IV standards in terms of total organic carbon, ammonium, nitrate and phosphate, while the RO membrane fouling was found to be insignificant in this process, evidenced by a dTMP/dt below 0.06 bar/day. In addition, more than 36% and 62% of reduction in footprint and excess sludge production could be achieved in the proposed integrated process against the current municipal wastewater reclamation process. Consequently, this part of study showed that the integrated MBCMBR-RO process could offer an alternative solution to alleviate water shortage, with small footprint and reduced sludge production. In the second phase of study, a ferrous-assisted aerobic granular sludge membrane bioreactor and reverse osmosis (AGSMBR-RO) process was developed for municipal wastewater reclamation. Results showed that about 99.9%, 99.7% and nearly 100% of dissolved organic carbon (DOC), NH4+-N and total phosphorus (TP) could be removed respectively in this process, while the product water could meet the typical NEWater quality of Singapore with respect to the major parameters analysed. Moreover, it was found that addition of 6 mg/L of ferrous could improve phosphorus removal as well as the stability of aerobic granular sludge through the coagulation and flocculation of suspended sludge. These in turn led to reduced membrane fouling in both AGSMBR and RO units. This phase of study provided a promising alternative for municipal wastewater reclamation. To further reduce the overall energy consumption and the sludge generation, a paradigm shift is needed for the conventional oxidation-based biological treatment process. In addition, driven by the circular economy and carbon neutrality campaign, it has been gradually realised that the nitrogen resource in municipal wastewater is totally lost in the form of nitrogen gas during the conventional biological nitrogen removal (BNR), which also results in large quantity of N2O generation. To tackle such an emerging issue, an integrated anaerobic fixed-film bioreactor (AnfBR) was employed in lieu of aerobic biological treatment for direct COD capture to produce methane with minimised sludge generation and enhanced energy recovery. A side-stream nanofiltration-reverse osmosis (NF-RO) in comparison of microfiltration-reverse osmosis (MF-RO) were implemented for subsequent high-grade water production. The product water from AnfBR-NF-RO process could meet the typical NEWater quality whereas the NH4+-N concentration of AnfBR-MF-RO permeate exceeded the typical NEWater quality (i.e., 1 mg N/L). The nitrogen and phosphorus which could not be consumed by anaerobic microorganisms were concentrated in RO brine, which could be further recovered. The third phase of this study clearly demonstrated the technological feasibility of AnfBR-NF-RO process, with the consideration of both sustainability and circular economy. To better improve the energy efficiency while reducing the greenhouse gas emission of the wastewater reclamation process as described in third phase of study, an integrated submerged fixed-film microfiltration membrane bioreactor (AnfMBR)-RO process was further employed in lieu of AnfBR-NF-RO, while a chlorination unit was implemented to serve as a polishing step to remove the excess NH4+-N. Results showed that about 99.9% of COD, 99.3% of phosphate and 95.3% of NH4+-N were removed in the AnfMBR-RO process, while breakpoint chlorination served as a polishing step in case that the NH4+-N concentration in RO permeate exceeded the typical NH4+-N concentration of NEWater (e.g., 1 mg/L). A comprehensive analysis on energy and GHG emission showed that the net energy consumption and total GHG emissions in the proposed process were 0.33 kWh/m3 and 504.7 g CO2e/ m3 wastewater treated, respectively, which were 63% and 68% less than those in the current wastewater reclamation process. It could be expected that the AnfMBR-RO-chlorination process could provide a feasible solution for sustainable municipal wastewater reclamation towards the energy and carbon neutrality. In conclusion, this study developed the alternative MBR-RO processes for municipal wastewater reclamation with low footprint, less energy consumption, reduced excess sludge generation and minimised GHG emission. Therefore, it can be expected that these novel processes with specific focus on water-energy-resource-GHG nexus may eventually game change future wastewater reclamation.